The pronoun use of housemaids to exhibit degree of respect when interacting with their superiors and the people related to their superiors - Pariña, Jose Cristina M. (Animo Repository, 2004)
This article demonstrates that pronouns in the Philippine context may also be used to exhibit respect just like in many cultures. The housemaids, which are the respondents of the study, are perceived to be a low type of job and so they are the ones who are most expected to adjust their language, specifically their use of pronouns, when dealing with people. Yet, the quantitative analysis done for the paper shows that housemaids now are not rigid in following the prescribed language feature, and that is, to always use the second person plural pronoun. Qualitative analysis on the other hand shows that, they can now adjust their language according to what they think are apt in a given situation. In addition, their language features, even if not polite in nature do not speak of the degree of respect that they have for people.